Strategi Pengembangan Bisnis UMKM Seni Lukis di Kampung Seni Jelekong, Bandung - Oktapian, Elsa; Wijaya, Fanji; Herlinawati, Erna; Mubarok, Dadan Abdul Aziz (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to analyze the development of painting UMKM in Kampung Jelekong, Bandung, focusing on marketing strategy and  SWOT analysis. Painting UMKM has great potential to develop and positively contribute to the local economy. However, they are also faced with various challenges in marketing their painting products and competing with an increasingly tight market. This research uses a qualitative approach with the case study method to collect data from various sources, including interviews with painting UMKM owners, field observations, and analysis of related documents. The collected data is then analyzed to identify opportunities and obstacles in developing the painting UMKM in Jelekong Village. The analysis results show that marketing strategies play an important role in driving the growth of painting UMKM. The keyword "painting" is the main key to introducing the products and attractiveness of Kampung Jelekong's unique paintings to prospective customers. Increasing public awareness about the uniqueness of painting is an important element in the marketing strategy. In addition, SWOT analysis also provides valuable insights for painting UMKM. The keyword "SWOT analysis" is the main key in identifying the strengths, weaknesses, opportunities, and threats faced by painting UMKM with a clear understanding of their position in the market and business environment; painting UMKM can design more effective and responsive development strategies. The results of this research are expected to provide valuable input for painting UMKM owners in Kampung Jelekong, Bandung, and other related parties, such as the local government and UMKM supporting institutions. By optimizing marketing strategies and properly using SWOT analysis, painting UMKM  in Kampung Jelekong can increase its competitiveness, face market challenges, and achieve sustainable growth